Simulation Performance Analysis of Shell and Tube Heat Exchanger Using Comsol Multiphysics 5.6 Software - Yety Setyo Ningrum; Ririn Martin Erinda; Made Arsana; Erlinda Ningsih; Anthony Francis Rajan (Journal of Mechanical Engineering, Science, and Innovation, 2023)
A heat exchanger is a very important tool in the fields of engineering and industry, especially in energy conversion. This study was aimed at determining the effects of hot and cold fluid flow velocity on the overall heat transfer coefficient (UA) and effectiveness in shell and tube heat exchangers using COMSOL Multiphysics 5.6 software. Another research objective was to observe the phenomena of heat transfer in the shell and tube type heat exchanger at each hot and cold fluid flow velocity. The heat exchanger was designed with a total length of 800 mm and equipped with 18 tubes having a diameter of 2 in and a length of 600 mm. The material used for tube and shell construction was stainless steel. A simulation was carried out using COMSOL Multiphysics 5.6 software to determine the performance of the designed heat exchanger. The results of this simulation indicated that the effects of hot and cold fluid velocity were directly proportional to the value of UA. The heat exchanger have result the smallest UA value of 80.062 W/m2.K, meanwhile the highest UA value of 174.950 W/m2.K. The heat exchanger have result the minimum effectiveness value of 22.305% and the maximum effectiveness value of 52,047%. The second result is phenomenon stating that the surface temperature of the shell and tube would change along with the increasing velocity of both hot and cold fluids, signifying the heat transfer such as conduction and convection from the fluid to the shell or tube.